Monsoons, ITCZs, and the Concept of the Global Monsoon. (1st December 2020) - Geen, Ruth; Bordoni, Simona; Battisti, David S.; Hui, Katrina
Abstract: Earth's tropical and subtropical rainbands, such as Intertropical Convergence Zones (ITCZs) and monsoons, are complex systems, governed by both large‐scale constraints on the atmospheric general circulation and regional interactions with continents and orography, and coupled to the ocean. Monsoons have historically been considered as regional large‐scale sea breeze circulations, driven by land‐sea contrast. More recently, a perspective has emerged of a global monsoon, a global‐scale solstitial mode that dominates the annual variation of tropical and subtropical precipitation. This results from the seasonal variation of the global tropical atmospheric overturning and migration of the associated convergence zone. Regional subsystems are embedded in this global monsoon, localized by surface boundary conditions. Parallel with this, much theoretical progress has been made on the fundamental dynamics of the seasonal Hadley cells and convergence zones via the use of hierarchical modeling approaches, including aquaplanets. Here we review the theoretical progress made and explore the extent to which these advances can help synthesize theory with observations to better understand differing characteristics of regional monsoons and their responses to certain forcings. After summarizing the dynamical and energetic balances that distinguish an ITCZ from a monsoon, we show that this theoretical framework provides strong support for the migrating convergence zone picture and allows constraints on the circulation to be identified via the momentum and energy budgets. Limitations of current theories are discussed, including the need for a better understanding of the influence of zonal asymmetries and transients on the large‐scale tropical circulation. Plain Language Summary: The monsoons are the moist summer circulations that provide most of the annual rainfall to many countries in the tropics and subtropics, influencing over one third of the world's population. Monsoons in different regions have historically been viewed as separate continent‐scale "sea breezes, " where land heats faster than ocean in the summer, causing warm air to rise over the continent and moist air to be drawn over land from the ocean. Here we show that recent theoretical advances and observational analyses support a novel view of monsoons as localized seasonal migrations of the tropical convergence zone : the band of converging air and rainfall in the tropics embedded within the tropical atmospheric overturning circulation. This updated perspective distinguishes the dynamics of low‐latitude (∼0–10° poleward) "Intertropical Convergence Zones" (ITCZs) from that of monsoons (∼10–25° poleward), explains commonalities and differences in behavior between the regional ITCZs and monsoons, and may help to understand year‐to‐year variability in these systems and how the global monsoon might change in the future. We end by discussing features that are not yet included in this new picture: the influence of mountains and continent shapes on the circulation and the relationship of the convergence zones with shorter‐lived weather systems. Key Points: Theoretical understanding of the dynamics of Hadley cells, monsoons, and ITCZs is developing rapidly Some aspects of observed monsoons and their variability can now be understood through theory Parallel theories should be reconciled and extended to account for zonal asymmetries and transients